1992
DOI: 10.1007/bf01715355
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral sinus thrombosis in a patient with hereditary protein S deficiency: Case report and review of the literature

Abstract: Hereditary protein S deficiency is an established risk factor for venous thrombosis. The common sites of thrombosis are the deep leg and pelvic veins. We report on a 38-year-old female patient with hereditary protein S deficiency and a previous history of deep leg vein thrombosis, who developed thrombosis of the cerebral straight and superior sagittal sinus while taking oral contraceptives. The diagnosis was established by computerized tomography and carotid angiography. Lysis of the thrombus occurred during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Despite the continuous description of new causes for CVT, to date, the fraction of cases with unknown cause is still more than 20%. [1][2][3][4][5][6][7] Recently, it has been reported that a G3 A transition at nucleotide position 20210 in the 3Ј-untranslated region of the prothrombin gene is associated with elevated plasma prothrombin levels and deep venous thrombosis. 8 The G 20210 3 A transition was found in a heterozygous form in 6.2% of 471 unselected consecutive patients with the first episode of deep venous thrombosis, but in only 2.3% of 474 healthy control subjects.…”
mentioning
confidence: 99%
“…Despite the continuous description of new causes for CVT, to date, the fraction of cases with unknown cause is still more than 20%. [1][2][3][4][5][6][7] Recently, it has been reported that a G3 A transition at nucleotide position 20210 in the 3Ј-untranslated region of the prothrombin gene is associated with elevated plasma prothrombin levels and deep venous thrombosis. 8 The G 20210 3 A transition was found in a heterozygous form in 6.2% of 471 unselected consecutive patients with the first episode of deep venous thrombosis, but in only 2.3% of 474 healthy control subjects.…”
mentioning
confidence: 99%
“…Prothrombotic states (factor V Leiden, protein S deficiency and protein C deficiency) have been reported in association with cerebral venous sinus thrombosis. [9][10][11] Investigation for these conditions was not possible due to the administration of anticoagulant therapy and/or presence of concurrent conditions. A routine coagulopathy screen was normal although disseminated malignancy may induce a prothrombotic tendency despite normal coagulation indices.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Possible aetiologies of cerebral venous sinus thrombosis include infection, 6 venous catheter associated thrombosis, 7 vasculitis, 8 or prothrombotic conditions. [9][10][11] We report three cases of cerebral venous sinus thrombosis following allogeneic bone marrow transplantation: in all three cases the diagnosis was made using MRA.…”
mentioning
confidence: 99%
“…The functional activity of protein S corresponds, for the most part, to the free form [6]. Clinical manifestations of protein S deficiency include leg vein thrombosis, pulmonary embolism, superficial thrombophlebitis and thromboses in uncommon sites [7,8].…”
Section: Anaesthesia; Obstetricmentioning
confidence: 99%
“…The functional activity of protein S corresponds, for the most part, to the free form [6]. Clinical manifestations of protein S deficiency include leg vein thrombosis, pulmonary embolism, superficial thrombophlebitis and thromboses in uncommon sites [7,8].Patients undergoing surgery are already at high risk of developing deep venous thrombosis and pulmonary embolism [9]. Normal pregnancy is also associated with hypercoagulable changes in the haemostatic system [ 101, and is one cause of acquired deficiency of protein S [I 1, 121.…”
mentioning
confidence: 99%